Sita’s Unresolved Pain: A Theoretical Analysis of Cultural Trauma in Valmiki’s Ramayana - Kyathari, Sridevi (Pastoral psychology, 2026)
Trauma theory provides a critical lens for examining the profound tragedy inherent in victims’ experiences, as exemplified by Sita in the Indian epic Ramayana. This study employs a trauma studies framework to re-examine Sita, the archetypal "ideal wife" in Valmiki’s Ramayana, revealing new dimensions of her suffering and its enduring cultural significance. Based on an analysis of key episodes of her abduction—the Agni Pariksha (fire trial), exile, and self-effacement—this study argues that Sita’s trauma and resilience transcend individual suffering to constitute a form of cultural trauma embedded in collective memory. The study used textual analysis and qualitative research methodology to explore the psychological and emotional impacts of Sita’s experiences and to highlight the complex interplay between gender, identity, and systemic oppression in the epic. It bridges trauma theory with Indian epic literature by investigating how Sita’s suffering transcends the personal to turn into generational trauma. By highlighting her trauma, this study emphasizes the unresolved psychological dimensions of her experiences and their lasting influence on the construction of women’s identities in Indian society.